Evolution of sub-ice-shelf channels reveals changes in ocean-driven melt in West Antarctica - Karen E. Alley; Richard B. Alley; Alex D. Crawford; Naomi Ochwat; Christian T. Wild; Juliana Marson; Tasha Snow; Atsuhiro Muto; Erin C. Pettit; Sarah F. Child; Martin Truffer; Gabriela Collao-Barrios; et al. (Journal of Glaciology)
Basal channels, which are troughs carved into the undersides of ice shelves by buoyant plumes of water, are modulators of ice-shelf basal melt and structural stability. In this study, we track the evolution of 12 large basal channels beneath ice shelves of the Amundsen and Bellingshausen seas region in West Antarctica using the Landsat record since its start in the 1970s through 2020. We observe examples of channel growth, interactions with ice-shelf features, and systematic changes in sinuosity that give insight into the life cycles of basal channels. We use the last two decades of the record, combined with contemporary ice-flow velocity datasets, to separate channel-path evolution into components related to advection by ice flow and those controlled by other forcings, such as ocean melt or surface accumulation. Our results show that ice-flow-independent lateral channel migration is overwhelmingly to the left when viewed down-flow, suggesting that it is dominated by Coriolis-influenced ocean melt. By applying a model of channel-path evolution dominantly controlled by ice flow and ocean melt, we show that the majority of channels surveyed exhibit non-steady behavior that serves as a novel proxy for increased ocean forcing in West Antarctica starting at least in the early 1970s.